Dearomatizing spirocyclization reactions of alkynyl cyanamides. Issue 29 (20th July 2016) - Singh, Ravi P.; Spears, Jada A.; Dalipe, Alfonso; Yousufuddin, Muhammed; Lovely, Carl J.
Graphical abstract: Highlights: Propargyl amine derivatives undergo dearomatizing spirocyclization. Unusual tandem cyanamidation-bromine-induced dearomatizing spirocyclization. Highly functionalized products and thus represent useful synthons. Abstract: Electrophile-induced dearomatizing spirocyclization reactions of propargylic cyanamides leading to cyclohexadienone derivatives are described. An unusual one-pot spirocyclization-N-cyanation reaction has been discovered leading directly to the spiro fused derivative. The products obtained through this chemistry may serve as key intermediates in synthetic approaches to several Leucetta alkaloids.